Higher Risk of Mortality and Virologic Failure in HIV-Infected Patients With High Viral Load at Antiretroviral Therapy Initiation: An Observational Cohort Study in Chongqing, China - Zhou, Chao; Zhang, Wei; Lu, Rongrong; Ouyang, Lin; Xing, Hui; Shao, Yiming; Wu, Guohui; Ruan, Yuhua (Frontiers in Public Health, 2022)
Background Viral load (VL) is a strong predictor of human immunodeficiency virus (HIV) disease progression. The aim of this study was to evaluate the influence of high baseline VL on antiretroviral therapy (ART) outcomes among HIV-infected patients. Methods This retrospective study observed HIV-infected patients who had baseline VL test at ART initiation between 2015 and 2019 in Chongqing, China. Cox proportional hazards regression and logistic regression models were used to evaluate the effects of baseline VL on mortality and virologic failure respectively. Results The cohort included 7176 HIV-infected patients. 38.7% of individuals had baseline VL results ≥5.0 log10 copies/mL, while 58.9% of treatment deaths occurred in baseline VL ≥5.0 log10 copies/mL group. Compared with VL <4 log10 copies/mL, ART initiation at VL ≥5.0 log10 copies/mL was significantly associated with the AIDS-related death (AHR=1.4) and virologic failure (AOR=2.4). Among patients with recommended first-line regimen, ART initiation at VL ≥5.0 log10 copies/mL had higher mortality rate than VL <4.0 log10 copies/mL (5.1 vs. 1.7), but there was no significant difference among second-line ART patients (2.8 vs. 2.7). Furthermore, ART initiation ≤30 d after HIV diagnosis decreased the risk of overall AIDS-related deaths (AHR=0.6). Conclusions ART initiation with VL ≥5.0 log10 copies/mL is significantly associated with a greater risk of mortality and virologic failure. Optimizing ART regimen and initiating ART early help reduce mortality effectively among patients with high baseline VL. It is recommended to provide VL test for all HIV patients at ART initiation or ahead at HIV diagnosis.